SMEs internationalisation in the Middle East - PHILIPPE, JOAN (2015)
Going abroad and expanding its geographical scope to foreign markets is not a strategy reserved to large corporations. It is, indeed, an important strategic option for both small and large organizations. With globalization of market and the increased of a more and more integrated world economy, we have “witnessed a rapid internationalization of markets, industries and firms” that took place in the early 1950’s (Olejnik & Swoboda. 2012).